GENEALOGICAL PERSPECTIVE OF THE LULUHYIA DIALECTS’ LEXICOSYNTACTIC SIMILARITIES - Lwangale, David Wafula; Bartoo, Dr. Phyllis J.; Mutiti, Prof. James K. (IJRDO- Journal of Educational Research, 2016)
The syntactic similarity of given languages may be used as evidence of their genealogical relatedness. This paper focuses on the lexicosyntactic similarities inherent across the Luluhyia dialects as evidence of their common origin. Despite the principle of language universals as advanced by Naom Chomsky leading to universal grammar (UG), not all languages of the world ascribe to the same syntactic structure. The findings of the study presented in this paper show that the Luluhyia dialects have the same syntactic structure as a result of the similarities of their lexical items. Such syntactic similarities across the Luluhyia dialects are an indicator of a once linguistically and anthropologically unified community whose origin was undisputedly one. The Luluhyia dialects use basically the same words only differing in pronunciation, stress placement and vowel length. In most cases, the distinction between the Luluhyia dialects cannot be detected by non-native speakers of the dialects. The variations are mostly suprasegmental in nature. However, the relatedness of the Luluhyia dialects is overtly displayed prompting a genealogical connection